1996
DOI: 10.1088/0953-8984/8/49/055
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of thin chromium nitride films: kinetics and morphology

Abstract: Magnetron-sputtered, 150 - 500 nm thick chromium nitride films of CrN and stoichiometry were exposed to air at 500 - . Oxide scale growth and morphology and the phase transformations during oxidation were investigated by means of Rutherford backscattering spectrometry, resonant nuclear reaction analysis, scanning force microscopy (SFM) and x-ray diffraction. A combined logarithmic and parabolic scale growth was found and interpreted as due to inwards diffusion of oxygen via grain boundaries (logarithmic) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
2

Year Published

2004
2004
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 24 publications
1
9
2
Order By: Relevance
“…This means that the oxidation rate tends to increase with increasing the fraction of grain boundaries, i.e. with decreasing the grain size [19]. Although this is in contrast to our results, the increasing oxidation resistance can be explained by increasing the thermal compressive stress with increasing the oxygen content.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…This means that the oxidation rate tends to increase with increasing the fraction of grain boundaries, i.e. with decreasing the grain size [19]. Although this is in contrast to our results, the increasing oxidation resistance can be explained by increasing the thermal compressive stress with increasing the oxygen content.…”
Section: Resultscontrasting
confidence: 99%
“…According to previous reports, the oxygen diffusion at grain boundaries is the fastest process in the oxidation of polycrystalline CrN coatings [19]. This means that the oxidation rate tends to increase with increasing the fraction of grain boundaries, i.e.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…It can be seen from the figure that reaction (3) has a much more negative Gibbs free energy; therefore alumina prefers to form. However, many previous results [27][28][29][30] indicated that the scales of CrAlN coatings consisted mainly of Cr 2 O 3 with some amounts of a-Al 2 O 3 dissolved in it. The reason for the formation of the oxide scales containing less a-Al 2 O 3 was explained by the fact that the aluminum content is low, and the activity of aluminum element is not high enough to forman a-Al 2 O 3 enriched scale.…”
Section: Discussionmentioning
confidence: 99%
“…The oxidation processes of CrAlN coatings have been studied widely by other researchers [24,[27][28][29][30], and the following two reactions are considered during oxidation of the coatings in an oxygen-containing atmosphere, Figure 8 gives the dependence of DG 0 on temperature. The thermodynamic data in the calculation are from Rao [31] and extrapolated to a wider temperature range.…”
Section: Discussionmentioning
confidence: 99%